Effects of shade and humus fertility on boreal forest tree seedling growth, competition and mycorrhizal colonisation - Dehlin, Helena (2005)
In boreal forest ecosystems, growth of tree seedlings is limited by resources both aboveground (through shading) and belowground (through nutrient limitation), and the ability to tolerate or avoid these conditions is important in determining the relative performance of different tree species. Two of the means to compete for these resources, are through increasing stem-elongation to escape shading by neighbours (shade avoidance), and through mycorrhizal symbiosis that may increase the nutrient- and water up-take. This experiment studies the effects of humus fertility and vegetation shade on the shade avoidance response, productivity, competitive ability and ectomycorrhizal (EM) colonisation of seedlings of the three major boreal tree species [Pinus sylvestris L., Picea abies (L.) Karst. and Betula pendula Roth]. The seedlings were grown in monocultures and in all possible two-species mixtures in pots containing humus collected from low- and high fertility sites in the boreal forest. They were then placed under light filters that were intended to simulate daylight (control) and two levels of partial shade by neighbouring plants by reducing light intensity (PAR) plus reducing light quality; i.e. the red: far-red ratio (R: FR). Three species of ectomycorrhizal (EM) fungi [(Paxillus involutus (Batch) Fr., Amanita muscaria (L.) Hooker and Laccaria bicolor (Maire) Orton] were added to each seedling, in order to assess the effects of the humus, shade, and seedling combinations on the relative EM root colonisation of the seedlings.